Reimagining learning through visual expression: the role of doodling as a pedagogical tool in fostering creativity and engagement in educational environments - Sharuddin, Raja Izwan; Isnin, Aiqa Afiqah; Azmin, Ahmad Faiz (Universiti Teknologi MARA, Perak, 2025)
In response to the evolving demands of 21st-century education, this study investigates the pedagogical potential of doodling as a transformative tool to enhance cognitive engagement, emotional expression, creativity, and inclusive learning. Traditionally dismissed as a distraction, doodling is reconsidered here as a multimodal strategy aligned with contemporary theories such as Constructivism, Dual Coding Theory, and Universal Design for Learning (UDL). Adopting a mixed-methods quasi-experimental design, this research compares the effects of doodling in experimental and control classroom settings, analysing outcomes through quantitative surveys, academic records, and qualitative interviews. Findings are expected to reveal that doodling significantly supports memory retention, emotional regulation, and creative problem-solving, especially in linguistically and culturally diverse classrooms. The study highlights inclusivity as a key moderating factor, amplifying the educational benefits of doodling for students with varied learning needs. Ultimately, the research advocates for the strategic integration of visual expression into curriculum design, reinforcing the importance of creative, inclusive, and student-centred pedagogies in enhancing both academic performance and holistic development.